Assessing the association between care quality and household chore rules in residential care institutions in Japan - Mizuki, Rie; Kyuzen, Mamiko; Nishizawa, Satoru; Mori, Shigeyuki (International Journal of Child, Youth and Family Studies)

(untitled) (University of Victoria, 2020)
The performance of household chores by children in Japanese residential care institutions has been widely accepted as a practice that fosters children’s independence and self-sufficiency. However, children coming from neglectful or dysfunctional families often require sensitive, individualized care, which they did not receive from their family of origin. While a shift away from large-scale institutions has begun, with smaller units or group homes now accounting for 40% of all care institutions, it is not clear that family-like, individualized care has been achieved in these smaller group homes. This study involved 61 participants aged 10 to 15 years and their care workers from six residential care institutions in the greater Tokyo area. It explored what aspects of care quality were related to the presence of certain characteristics of traditional management-oriented care: fixed rules for household chores and lack of choice in daily living. Care workers were asked whether children washed their own dishes, did their own laundry, chose their own clothes when shopping, and had mandatory events to attend in the residential care institutions. Care quality was assessed using the Early Adolescent HOME (Home Observation for Measurement of Environment) developed for Japanese residential care institutions (EA-HOME-JP). The findings suggest that care workers should re-examine their intentions in setting and applying household chore rules while exploring which aspects of child care, including regulatory activities and modeling, should be emphasized in order to actualize family-like and individualized care in institutions.